Mapping the evolution of PET/MR research: a bibliometric analysis of publication trends, leading contributors, and conceptual frameworks (2011–2023) - Li, Jiajin; Ye, Chuntao; Li, Shihong; Lin, Guangwu (EJNMMI reports, 2024)
Background Positron emission tomography-magnetic resonance imaging (PET/MR) is a cutting-edge hybrid imaging technology with the potential to revolutionize medical diagnosis. This bibliometric study aims to map the research landscape of PET/MR by analyzing a curated set of Web of Science Core Collection documents from 2011 to 2023. Methods We conducted a bibliometric analysis to map the research landscape of PET/MR, leveraging a curated dataset of 3,600 documents retrieved from the Web of Science Core Collection spanning the period from 2011 to 2023. We employed quantitative methods to assess the quantity and distribution of PET/MR studies, including patterns of change, research status, and directions. Additionally, we utilized VOSviewer software to conduct keyword co-occurrence analysis, explore collaborative networks among authors and institutions, and identify influential journals in the field. Results Results: The analysis reveals several key insights: (1) a significant increase in the number of PET/MR publications over the past 12 years, highlighting the growing interest and activity in this field; (2) the United States and Germany as the leading countries in terms of research output and collaboration, with a growing presence of other countries such as China; (3) the Journal of Nuclear Medicine and the European Journal of Nuclear Medicine and Molecular Imaging as the most influential journals in the field; (4) a shift in research focus from imaging techniques to clinical applications, with an increasing emphasis on prostate cancer, PSMA, and FDG imaging. Conclusions This study provides a comprehensive overview of PET/MR research, identifying prominent trends, key researchers, and influential works. Based on these findings, we propose recommendations for future research directions in this rapidly evolving field.